Automonitoramento do consumo de água em lavouras de arroz irrigado utilizando vertedores triangulares - Pascotini, Pedro Brites (2014)
The irrigated rice contributes immensely in water consumption in Brazil. Wuth intention of inducing its rational use, the country has juridical and institutional procedures, including the granting of water use. However, the effectiveness of this instrument it is necessary the control of the granted volumes. Thus, looking instruments to quantify these volumes and can serve as possible supervisory of the granted volumes, one of them is self-monitoring. Thus, the study aims to contribute to the management of water resources, seeking to validate a simplified and cost-effective for self-monitoring of the water volumes used in rice fields. The study was implemented in São Pedro do Sul county in the 2013/14 season, where were performed self-monitoring by means of triangular weirs on two rice plots, one with uptake in river and dam in another. The areas of these plots are 2.6 ha and 27.0 ha, respectively. To validate and simplify the system of self-monitoring, sought to evaluate whether two daily measurements of hydraulic head over the spillways are sufficient to represent the possible variations in the channels and estimate the total volume of water used by the rice crop. The evaluation was performed using the parametric Student's t test for a mean in order to compare the actual and the estimated volume by two measurements. To define the charge passing through the hydraulic structure and defines the flow when applied to the spillway key curve was used graduated rulers and automatic level sensors Solinst ®. For quantification of water intake in rice fields by precipitation, a rain gauge was used, and this precipitation was added to the volume irrigated to define the total volume of water demanded in each area. For both plots monitored, the actual volume and the estimated two measurements showed no significant difference to the significance level of 0.05. The volumes used by crops monitored in this season, showed the average of two parcels an irrigated volume 16% lower than the grantee. In short, the quantification of the volume used in rice crops, through self-monitoring system proposed, with simplified methods of flow measurement, in the different arrangements of irrigation presented, was suitable for use in large-scale measurement of volumes granted, as subsidy for water resources management. Self-monitoring by means of triangular weirs, with the realization of just two daily measurements of the spillways levels is efficient to estimate the total volume of water demanded by rice fields, presenting satisfactory representation of the daily variation in water level observed in the channels. The study also demonstrates that the data collected by the sensors are more precise than the data defined by the level of water in the graduated rulers, but even with the use of these lower accuracy is satisfactory.